Relationship of the number and size of superficial groin lymph nodes with the stage of secondary lymphatic edema. Issue 8 (6th October 2016) - Onoda, Satoshi; Kimata, Yoshihiro; Yamada, Kiyoshi; Seki, Noriko; Hiramatsu, Yuji
Abstract : Purpose: This study evaluated the relationships of the size and number of superficial groin lymph nodes with the lower limb lymphedema stage and thus examined the role of superficial lymphatic lymph nodes in secondary lymphedema development. Methods: We determined the number and size of superficial groin lymph nodes using horizontal plane computed tomography (CT) and the lymphedema stage in the lower limbs of 25 patients with gynecologic cancer. Results: The patients had an average of 2.92 (range, 1–7) superficial groin lymph nodes; the mean size of the 146 evaluated lymph nodes was 7.55 mm (range, 5–15 mm). In 19 of 25 patients (76%), the side with major edema contained fewer superficial groin lymph nodes. In total, 22 patients (88%) had fewer superficial groin lymph nodes or a smaller total lymph node size on the edematous dominant side. Conclusions: In this evaluation of the link between superficial groin lymph node laterality and secondary lymphedema staging, we found that patients with large lymph node numbers and sizes tended to present with a relatively earlier stage of lymphedema. Our results therefore suggest that the size and number of superficial groin lymph nodes affect the lymphedema stage. J. Surg. Oncol. 2016;114:940–946 . © 2016 Wiley Periodicals, Inc.